EFEKTIFITAS TEKNIK ART THERAPY UNTUK MEREDUKSI ACADEMIC BURNOUT MAHASANTRI IBNU KATSIR PUTRI JEMBER - Majid, Shabrina; Rahmawati, Weni Kurnia; Fauziyah, Nailul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effectiveness of art therapy techniques in reducing academic burnout among female students (mahasantri) at the Ibnu Katsir Islamic Boarding School in Jember. Academic burnout refers to a state of physical and emotional exhaustion caused by excessive academic pressure, often accompanied by apathy toward academic tasks and a decline in learning motivation. The demanding academic environment and intensive boarding school life may increase the risk of burnout among mahasantri. Therefore, appropriate interventions are needed to help address academic burnout and improve psychological well-being. Art therapy was chosen as a method believed to alleviate stress and emotional fatigue. The study employed an experimental design with a control group. Participants were divided into two groups: an experimental group that participated in art therapy sessions and a control group that received no intervention. Burnout levels were measured before and after the intervention using a standardized burnout questionnaire. This study aims to assess changes in burnout levels, identify the most affected burnout components (physical, emotional, and cynical attitudes), and provide recommendations for implementing art therapy in pesantren settings. The findings are expected to offer empirical evidence of the effectiveness of art therapy in reducing academic burnout and to contribute to the literature on psychological interventions in religious educational environments.